Factors Influencing the Student Enrolment Rate at Higher Education in Nepal - Devkota , Krishna Maya; Tamrakar, Pratima; Timilsna , Narayan Prasad (Innovative Research Journal, 2025)
This study is carried out to explore the factors influencing students' enrolment rates in higher education at Tribhuvan University (TU). It is a mixed-method study that employs a convergent mixed-method design. Data were collected from 384 students and 6 teachers with the educational authorities of TU by using surveys and in-depth interviews. The data were analyzed through descriptive statistics and thematic analysis in convergent form. Findings revealed strong socio-economic and personal influences, with over 60% of students reporting monthly family incomes below NPR 15,000, and financial obstacles to enrolment. A large majority (67.4%) were aged 25 to 29, reflecting delayed entry, as many worked first to save for enrolment. Females comprised 59.6% of respondents, indicating higher female participation partly due to male labor migration abroad. Motivation for enrolment centered on future job security (50.8%) and social prestige, with families and teachers providing critical encouragement. Nearly 70% were first-generation university students. Academic and institutional factors also shaped access. 64.1% of students participated from master's program, while the Humanities faculty had a good representation (42.4%) in this study. Still, institutional and systemic barriers persisted, only 21.6% believed scholarships were easily available, fewer than 40% were satisfied with the enrolment process, and limited information, housing, and transport created big challenges. Overall, the study highlights the need for enhanced financial support, clearer communication, and inclusive support policies to improve equitable enrolment at TU.